The basics of pedagogical activities in recreational activities for children and young people - Koskela Olli; Tuominen-Suarez Virve; Yli-Ollila Marika; Marvin Elisa; Hyttinen Hilkka; Jaakkola Kirsi; Kähkönen Olli; Katajisto Joanna; Setälä Veijo; Furman Ben; Lammassaari Heidi; Ylirisku Henrika; et al.
The videos and the related lecture slides have been produced as part of the online training The basics of pedagogical activities in recreational activities for children and young people, which was implemented seven times between 2022 and 2024. In addition, there are development tasks included, which are examples of students’ course outcomes of the training. More than 600 supervisors of recreational activities and a total of 15 lecturers participated in the free and open training. These videos are separately filmed summaries of the themes of the lectures presented in the course. The actual lectures were delivered live via a remote connection. The training was initially a part of the national child strategy and subsequently a part of the development of the Finnish Model for Leisure Activities. It was aimed at supervisors of sports, art, culture and other hobbies. The first implementation of the training was organised in summer 2022. All trainings were carried out in accordance with the same curriculum and they corresponded in terms of content. The training included remote lectures, small group work, peer mentoring, online discussions and pedagogical development tasks. The key themes of the training were the quality of recreational activities for children and young people and the development of pedagogy, as well as the development stages of children and young people. These topics and current information in the field were discussed under the guidance of top Finnish experts in special education, constitutional law, psychiatry, education and psychology as well as arts and physical education. The training was organised by the Open Campus of Uniarts Helsinki and the Observatory for Arts and Cultural Education, Finland in cooperation with the Olympic Committee. The training was funded by the Ministry of Education and Culture. The videos produced during the training have been subtitled in Finnish, Swedish, English, Russian and Northern Sámi.